The thing itself of language in the work of Giorgio Agamben. A review of the concept of community - Pino Estivill, Ester (Romanica Olomucensia, 2014)
This present article takes Giorgio Agamben's conception of language as a "thing itself", a recurring theme on his work, as a starting point to understand his political position, culminates with an invitation to the coming community. Through his genealogical reading of the gaps between discourse and language, the key elements of his philosophy are revealed, such as the Aristotelian reading of nous and the power of thought. Drawing upon his conception of language as a space devoid of belongings, the article seeks to review the concept of community in dialogue with other contemporary philosophers as Maurice Blanchot, Jean-Luc Nancy and Roberto Esposito.
Keywords: Agamben; language; power; thought; community.